The Application Of System Based Models Victim Offender Mediation Towards Recovery Of State Financial Losses Due To Corruption In Indonesia - Sidabutar, Victor Antonius Saragih; Febrian, Febrian; Nashriana, Nashriana; Achmad, Ruben (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In some cases, corruption has the potential to develop into money laundering, which will complicate the performance of law enforcement officers to track suspicious financial transactions and save assets suspected of belonging to the state. In response to this problem, the replacement money payment system is carried out by law enforcement officers. However, based on the results of the investigation, the implementation of replacement money payments for the recovery of state financial losses is considered ineffective and inefficient at the application and execution stages. Therefore, a legal breakthrough is needed in the form of the use of penal mediation as an effort to maximize state financial recovery. The purpose of this study is to identify the problems of recovering state financial losses due to corruption in Indonesia and the application of the victim offender mediation system based models to recovering state financial losses due to corruption in Indonesia. The results of this study indicate that the alternative nature contained in the construction of Article 18 of Law. No. 31 of 1999 has the potential to result in efforts to recover state financial losses being less than optimal and effective, this is due to the tendency of perpetrators to avoid responsibility for paying replacement money. The application of SBM VOM to recovering state financial losses can be done by accommodating the concept of PB in positive law in Indonesia. This research is a normative legal research using 3 approaches, namely the statutory approach (Statute Approach), the conceptual approach (Conceptual Approach) and the comparative approach (Comparative Approach).